Response of fenugreek (Trigonella foenum-graecum L.) to plant growth regulators and their time of application - Sastry, S S Rajput, A C Shivran, N L Jat, D Singh, E V D (Journal of Spices and Aromatic Crops, 2016)
The effect of plant growth regulators and their time of application on growth, yield and economics of fenugreek were studied during three winter seasons (Rabi) of 2005–06 to 2007–08. Plant growth regulators used were Naphthalene Acetic Acid (NAA) 50 ppm, Triacontanol 1000 ppm & Triacontanol 500 ppm with three times of spray viz., one (40 DAS), two (40 & 60 DAS) and three (40, 60 & 80 DAS) along with absolute control laid out in factorial randomized block design replicated thrice. Based on three years study it was observed that growth regulator treatments significantly influenced growth, yield attributes, yield & economics of fenugreek. The highest pods plant-1, test weight, seed yield (1494 kg ha-1), straw yield (3381 kg ha-1), gross returns (Rs. 51582 ha-1), net returns (Rs.35586 ha-1) and benefit : cost ratio (2.25) were recorded with NAA 50 ppm which was significantly superior to Triacontanol 1000 ppm & 500 ppm & water spray. The seed yield was increased by 27.80%, 23.70% & 16.08% and net returns by 44.20%, 36.71% & 25.25% with application of NAA 50 ppm, Triacontanol 1000 ppm & 500 ppm over spray of water, respectively. Further, significantly maximum number of branches plant-1, test weight, seed yield (1409 kg ha-1), gross returns (Rs. 48546 ha-1), net returns (Rs. 32331 ha-1) and benefit : cost ratio (1.99) were recorded with three sprays at 40, 60 & 80 DAS closely followed by two sprays at 40 & 60 DAS over single spray at 40 DAS. Hence, the application of NAA 50 ppm twice at 40 & 60 DAS or thrice at 40, 60 & 80 DAS was found beneficial in terms of increased growth, yield and monetary returns of fenugreek.